Spatial Assessment of Carbon Emissions Caused by Industrial Activities in Batang Anai, West Sumatra - Novelia, Nabila; Putri, Rozana Eka; Ulni, Arie Zella Putra (Jurnal Penelitian Geografi, 2025)
This study aims to analyze: (1) the spatial distribution of carbon emissions in Batang Anai District, Padang Pariaman Regency, and (2) the impacts of carbon emissions on environmental quality and community settlements. The primary focus is to map emission patterns while also assessing their socio-economic and public health implications. A descriptive quantitative method with a spatial analysis approach was applied, utilizing Geographic Information System (GIS) techniques supported by ArcGIS software. Data collection included field surveys, interpretation of land cover imagery from 2015 and 2025, estimation of potential carbon stocks, and questionnaire distribution to residents within a 2-km radius of industrial areas across three villages (Kasang, Katapiang, and Sungai Buluh). Analytical procedures involved overlaying carbon emission and land cover maps, calculating carbon concentrations, and processing perception data using a Likert scale to assess environmental, health, and socio-economic impacts. The results reveal: (1) the spatial distribution of carbon emissions is categorized into three levels—low, medium, and high; and (2) communities report deteriorating air quality, increased dust and air temperatures, respiratory illnesses, and reduced living comfort. These findings highlight the urgent need for industrial zoning-based carbon emission control and the establishment of vegetative buffers around industrial zones to enhance environmental sustainability and community well-being.